Pembentukan Kader Remaja Anti-Anemia Pencegah Stunting (Ranting) dengan Pemanfaatan Kearifan Lokal di Puskesmas Durian Luncuk - Maharani, Sri; Safitri, Safitri; Gustrajeky, Andicha (Universitas Baiturrahim, 2024)
Teenagers are one of the focuses of government intervention in national action to tackle stunting. The first 1000 days of life, starting from conception until the 2nd age, is a critical time for optimal mother and child nutrition. Indonesian teenagers experience three nutritional problems, namely shortness (2.5%), too thin (8%), obesity (15%), and anemia (23%). Based on Minister of Health Regulation Number 39 of 2016, one of the efforts made to reduce the prevalence of stunting is to increase education and counseling for clean and healthy living behavior (PHBS) and balanced nutritional patterns in adolescents. Handling and preventing anemia can be done by consuming foods that contain vitamins and minerals which support the formation of red blood cells as prevention, fortifying foodstuffs with iron, and iron supplementation. Consume a variety of foods rich in iron, folate, vitamin B12 and vitamin C. Apart from that, additional iron intake is also provided from blood supplement tablets (TTD). This PkM activity will be held in September 2024 with a total of 43 participants. The method used in this PkM is to provide health workers, midwife training and cadre training. The instrument used to measure knowledge uses a questionnaire. The duration of this PkM activity is 8 hours per meeting session. The results of community service activities were the formation of anti-anemia youth cadres to prevent stunting (Ranting), increasing knowledge of teenagers, namely 81.5%, teenage cadres 81% and village midwives 21%. The conclusion is that in implementing this community service, there is an increase in knowledge among youth groups, youth cadres and village midwives, as well as the formation of anti-anemia youth cadres to prevent stunting (Ranting).